2020
DOI: 10.3390/jcm9082402
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Atrial Fibrillation in Patients with Hypertension—An Analysis from the German Ablation Registry

Abstract: Background: Hypertension (HTN) constitutes a risk factor for the development of atrial fibrillation (AF), as well as for thromboembolic and bleeding events. We analysed the outcome after catheter ablation of AF in HTN in a cohort from the prospective multicenter German Ablation Registry. Methods: Between 03/2008 and 01/2010, 626 patients undergoing AF-ablation were analysed. Patients diagnosed with HTN (n = 386) were compared with patients without HTN (n = 240) with respect to baseline, procedural and long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
1
5
1
Order By: Relevance
“…Moreover, we observe the same for stroke and MACCE [Mack 2019;Mäkikallio 2016;Popma 2019;Serruys 2009;Stone 2016]. Also, no patient in our SR-group suffered a complication, which are more likely to occur in interventional ablations (where it is around 0.5%, i.e., pulmonary vein injury or stenosis, phrenic nerve palsy, vena cava, or esophageal injury [Kany 2021;Rottner 2021;Zylla 2020]). In addition, only 0.3% of patients in the SR group had a pulmonary embolism.…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, we observe the same for stroke and MACCE [Mack 2019;Mäkikallio 2016;Popma 2019;Serruys 2009;Stone 2016]. Also, no patient in our SR-group suffered a complication, which are more likely to occur in interventional ablations (where it is around 0.5%, i.e., pulmonary vein injury or stenosis, phrenic nerve palsy, vena cava, or esophageal injury [Kany 2021;Rottner 2021;Zylla 2020]). In addition, only 0.3% of patients in the SR group had a pulmonary embolism.…”
Section: Discussionsupporting
confidence: 67%
“…The effect of hypertension on atrial fibrillation recurrence after ablation is influenced by the level of control of this risk factor. Hypertension associates with increased age, more cardiovascular comorbidities, greater likelihood of persistent AF, and was an independent predictor of increased recurrence of AF post-ablation in earlier studies [63][64][65][66]. A more recent study of 626 patients from 55 centres in the German Ablation Registry showed that AF recurrence rates, freedom from antiarrhythmic medication and repeat ablation were not different with versus without hypertension diagnosis at the time of ablation, though there were more reports of dyspnoea, angina and more re-hospitalisations in those with hypertension [66].…”
Section: Hypertension and Ablationmentioning
confidence: 75%
“…Hypertension associates with increased age, more cardiovascular comorbidities, greater likelihood of persistent AF, and was an independent predictor of increased recurrence of AF post-ablation in earlier studies [63][64][65][66]. A more recent study of 626 patients from 55 centres in the German Ablation Registry showed that AF recurrence rates, freedom from antiarrhythmic medication and repeat ablation were not different with versus without hypertension diagnosis at the time of ablation, though there were more reports of dyspnoea, angina and more re-hospitalisations in those with hypertension [66]. A further multi-centre study of 531 consecutive patients undergoing AF ablation showed again that hypertension itself was not associated with a higher recurrence rate of AF following AF ablation, but poor control of hypertension despite medical therapy pre-procedure did lead to higher recurrence [65].…”
Section: Hypertension and Ablationmentioning
confidence: 75%
“… 412 In contrast, a registry analysis showed that patients with a diagnosis of hypertension, without information regarding the efficiency of antihypertensive management, had similar rhythm outcome after catheter ablation to those without hypertension. 438 In the SMAC-AF randomized trial, short-term aggressive blood pressure (BP) treatment (target systolic BP ≤120 mmHg) for a median duration of 3.5 months before scheduled AF catheter ablation in patients with hypertension did not reduce arrhythmia recurrence following ablation when compared with standard BP treatment (target systolic BP <140 mmHg). 439 Although treating modest hypertension in isolation has not proven to be of benefit, when undertaken in the setting of a comprehensive risk factor management programme in overweight and obese individuals, it has been associated with higher rate of SR maintenance after catheter ablation.…”
Section: Atrial Fibrillation Risk Factors and Preprocedural Managementmentioning
confidence: 99%